The Role of Polyphenols in Human Health and Food Systems: A Mini-Review - Cory, Hannah; Passarelli, Simone; Szeto, John; Tamez, Martha; Mattei, Josiemer (Frontiers in Nutrition, 2018)
This narrative mini- review summarizes current knowledge of the role of polyphenols in health outcomes – and non-communicable diseases specifically – and discusses the implications of this evidence for public health, and for future directions for public health practice, policy, and research. The publications cited originate mainly from animal models and feeding experiments, as well as human cohort and case-control studies. Hypothesized protective effects of polyphenols in acute and chronic diseases, including obesity, neurodegenerative diseases, type 2 diabetes, and cardiovascular diseases, are evaluated. Potential harmful effects of some polyphenols are also considered, counterbalanced with the limited evidence in the research literature and recent disproof by some international governmental regulatory bodies. The implications of food processing on the bioavailability of polyphenols are also assessed, in addition to the health claims and marketing of polyphenols as a functional food. Finally, this mini-review asserts the need for increased regulation and guidelines for polyphenol consumption and supplementation in order to ensure consumers remain safe and informed about polyphenols.